Immobilized MAS1 lipase showed high esterification activity in the production of triacylglycerols with n-3 polyunsaturated fatty acids. (1st February 2017) - Wang, Xiumei; Li, Daoming; Qu, Man; Durrani, Rabia; Yang, Bo; Wang, Yonghua
Highlights: Macroporous absorption resin XAD1180 was used to immobilize lipase MAS1. The immobilized MAS1 was employed to produce n-3 PUFA-rich TAG by only one step enzymatic esterification. Highly pure (92.26%) n-3 PUFA-rich TAG with high content of n-3 PUFA was obtained. The immobilized MAS1 exhibited better catalytic properties in synthesis of n-3 PUFA-rich TAG than Novozym 435. DAG content was almost negligible and not accumulated in the reaction process. Abstract: Immobilization of lipase MAS1 from marine Streptomyces sp. strain W007 and its application in catalyzing esterification of n-3 polyunsaturated fatty acids (PUFA) with glycerol were investigated. The resin XAD1180 was selected as a suitable support for the immobilization of lipase MAS1, and its absorption ability was 75 mg/g (lipase/resin ratio) with initial buffer pH value of 8.0. The thermal stability of immobilized MAS1 was improved significantly compared with that of the free lipase. Immobilized MAS1 had no regiospecificity in the hydrolysis of triolein. The highest esterification degree (99.31%) and TAG content (92.26%) by immobilized MAS1-catalyzed esterification were achieved under the optimized conditions, which were significantly better than those (82.16% and 47.26%, respectively) by Novozym 435. More than 92% n-3 PUFA was incorporated into TAG that had similar fatty acids composition to the substrate (n-3 PUFA). The immobilized MAS1 exhibited 50% of its initial activity after being used for five cycles.